2014
DOI: 10.1097/tp.0000000000000028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Obesity on Kidney Transplantation Outcomes

Abstract: In conclusion, obese patients have increased risk for DGF. In the past years, obesity was a risk factor for graft loss, death by CVD, and all-cause mortality. However, for the obese transplanted patient today, the graft and patient survival is the same as that of the nonobese patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
122
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(134 citation statements)
references
References 42 publications
5
122
0
7
Order By: Relevance
“…In terms of survival, obese patients tend to have no decrease in short-term survival but may have attenuated overall survival; however, whether this is related to a decrease in graft function or other obesity-related effects is undetermined (27,33). In terms of graft survival, acute rejection tends to be increased in obese patients (27,34,37), and obesity is associated with delayed graft function in kidney transplantation (29)(30)(31)(32), hepatocellular carcinoma in liver transplants (27,33), and grade III primary graft dysfunction in lung transplants (27).…”
Section: How Does Obesity Affect Solid Organ Transplantation?mentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of survival, obese patients tend to have no decrease in short-term survival but may have attenuated overall survival; however, whether this is related to a decrease in graft function or other obesity-related effects is undetermined (27,33). In terms of graft survival, acute rejection tends to be increased in obese patients (27,34,37), and obesity is associated with delayed graft function in kidney transplantation (29)(30)(31)(32), hepatocellular carcinoma in liver transplants (27,33), and grade III primary graft dysfunction in lung transplants (27).…”
Section: How Does Obesity Affect Solid Organ Transplantation?mentioning
confidence: 99%
“…Studies have also been performed in the context of pancreas, lung, and heart transplantation, but their statistical power is limited due to small patient numbers. Generally, these epidemiological studies show that obese transplant recipients have more perioperative morbidities and tend to have longer hospital stays, possibly related to the obesity-associated risks of infection, sepsis, and longer ischemia times (27,(29)(30)(31)(32)(33)(34)(35)(36). In terms of survival, obese patients tend to have no decrease in short-term survival but may have attenuated overall survival; however, whether this is related to a decrease in graft function or other obesity-related effects is undetermined (27,33).…”
Section: How Does Obesity Affect Solid Organ Transplantation?mentioning
confidence: 99%
“…Adult studies report widely on the strong association between delayed graft function and obesity [17][18][19][20][21][22]. Some of the reasons for this association may relate to the technical challenges at the time of surgery, including a prolonged anastomotic time leading to longer warm ischaemia duration, whilst others may be related to the type of donor (donation after circulatory death) or the negative impact of higher calcineurin inhibitor doses.…”
Section: Graft Functionmentioning
confidence: 99%
“…However, a similar correlation at both ends of the BMI spectrum has not been described in the paediatric population. A recent meta-analysis suggested that in fact the association between BMI and poorer adult patient and graft survival was only present in the early reported studies and has been non-existent in studies conducted during the last 10 years [21] (Fig. 2).…”
Section: Patient and Graft Survivalmentioning
confidence: 99%
See 1 more Smart Citation